THE CORRELATION BETWEEN STUDENTSâ KNOWLEDGE IN VOCABULARY AND THEIR READING COMPREHENSION - Yanpitherszon, Liunokas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2016)
This research aimed at describing the correlation between the mastering vocabulary in English and the studentsâ ability in reading comprehension at the first year students. This research applied descriptive research by using vocabularies and reading comprehension test.Â  The population of this research was the first year students at SMA. The total number of population was 51 students. The population consisted of three classes namely A, B, C.Â  the researcher used cluster random sampling technique inÂ  determining 20 students of class IPA 1 as a sample.Â  The instruments that were used in this research were vocabulary test and reading comprehension test in the form of multiple-choice 40 numbers. The test was used to find the studentâs ability in mastering vocabulary and the studentâs ability in reading comprehension at the first year of SMA Datok Sulaiman Putri Palopo. The result of the research shows that the vocabulary of students have significant contribution towards the studentsâ reading score.Â  It is proven by the result of the correlation test using Pearson Product Moment with SPSS 20 software program, it is found that the score significance is 0.302.Â  The score significance is higher than Î± score (0.302â¥ 0.05).Â  It is classified as a low correlation.Â  It is based on the classification of coefficient correlation (0.20-0.39). It indicates that when the students have a good vocabulary, it will have contribution towards their competence in reading. The vocabulary mastery can give good influence to his or her reading result.